ESG Implementation, Transparency of Sustainability Reporting, and Corporate Governance on Stock Value Through Manufacturing Company Reputation on the Indonesia Stock Exchange - Idris, Hariany (PINISI Discretion Review, 2025)
ESG and transparency of sustainability reporting are increasingly becoming major concerns in the business world, as investor awareness of non-financial aspects in investment decision making increases. Good corporate governance is believed to be able to strengthen credibility and increase public trust. Corporate reputation is considered to have an important role in shaping investor perceptions of the company's long-term prospects. The study aims to analyze the effect of Environmental, Social, and Governance (ESG) implementation, transparency of sustainability reporting, and corporate governance on stock value, with corporate reputation as a mediating variable in manufacturing companies on the Indonesia Stock Exchange. Associative quantitative research approach. The population consists of manufacturing companies listed on the IDX in 2022–2024 totaling 222 companies. The sample size is 84 companies and the number of data is 252 data. The sample collection technique uses purposive sampling. Secondary data sources are annual reports, sustainability reports, Bloomberg/RTI, IDX, and company websites. Data analysis tools use SEM-Amos and Sobel Test. This study indicates that improving the quality of ESG (Environmental, Social, and Governance) implementation has a significant impact on strengthening corporate reputation. Transparency in sustainability reporting also contributes positively by building trust from the public and investors. The implementation of effective corporate governance strengthens the image and supports business continuity. Furthermore, the quality of ESG and transparency of sustainability reports also support the increase in stock value through positive investor perceptions. In this process, the company's reputation functions as a mediator between ESG implementation, reporting transparency, and governance with stock value. A strong reputation increases investor confidence, thus driving an increase in the company's stock value.